Perioperative Venous Thromboembolism in Ulcerative Colitis: A Multicenter Prospective Study in Japan. Issue 3 (23rd May 2021) - Itabashi, Michio; Ikeuchi, Hiroki; Kimura, Hideaki; Fukushima, Kohei; Fujii, Hisao; Nezu, Riichiro; Futami, Kitaro; Sugita, Akira; Suzuki, Yasuo; Hisamatsu, Tadakazu
Abstract: Background: Recently, the prevalence of venous thromboembolism (VTE) in Asian patients with inflammatory bowel disease (IBD) is gradually increasing. IBD surgery is a well-recognized risk factor for VTE. However, there are no prospective studies about VTE after surgery for ulcerative colitis (UC) in Asia. This multicenter prospective study aimed to clarify the prevalence and risk factors for perioperative VTE in UC surgery in Japan. Methods: A total of 134 patients with UC were included from January 1, 2013 to December 31, 2014. Preoperative screening was performed in all patients. In the perioperative period, standard VTE prophylaxis based on risk assessment was administered. The prevalence of pre- and postoperative VTE, its risk factors, and mortality rates were investigated. Results: Perioperative deep vein thrombosis and pulmonary embolism were diagnosed in 15 (11.1%) and 1 patient (0.7%), respectively. All patients were asymptomatic. No surgery-related deaths were found (mortality rate 0%). Seven patients (5.2%) were diagnosed, and 8 (6.4%) during postoperative follow-up by ultrasonography or computed tomography. Forty-seven percent of VTE cases was developed preoperatively. A preoperative hospital length stay of over 5 days was a significant risk factor [ P = 0.04; odds ratio: 8.26 (1.06–64.60)] for preoperative VTE. Postoperative deep vein thrombosis occurred in 8 of the 127 patients (6.4%). Six out of these 8 (75.0%) occurred after postoperative day 14. Perioperative blood transfusion was a significant risk factor [ P = 0.04; odds ratio: 8.26 (1.06–64.60)] for postoperative VTE. Conclusion: A VTE-conscious perioperative management is as necessary in Asia as in Western countries. Lay Summary: This is the first scheduled venous thromboembolism (VTE) study in ulcerative colitis surgery in Asia. Deep vein thrombosis and pulmonary embolism were diagnosed in 11.1% and 0.7% of 134 patients during the surgical period. Even in Asia, VTE-conscious perioperative management is necessary.